Association of Sedentary Lifestyle With Skeletal Muscle Strength and Mass in US Adolescents: Results From the National Health and Nutrition Examination Survey (2011-2014) - Kun-Hee Oh; Jin-Young Min; Kang Seo; Kyoung-Bok Min (Journal of Preventive Medicine and Public Health)
Objectives: Excessive sedentary behavior in youth is a major global issue, contributing to the rise in childhood obesity and metabolic diseases. International public health authorities have issued guidelines recommending that children and adolescents limit their daily sedentary time, including screen time. However, to date, no studies have explored the relationship between sedentary behavior as an exposure factor and skeletal muscle strength and mass as outcomes in this population. The present study investigated the association of sedentary behavior with handgrip strength (HGS) and appendicular lean mass (ALM) among United States adolescents. Methods: A total of 1449 adolescent participants from the National Health and Nutrition Examination Survey (2011-2014) were included. Information on sedentary behavior, specifically daily sedentary time, was obtained through a self-reported questionnaire. Muscular parameters, including HGS and ALM, were measured. To adjust for differences in body size, these parameters were divided by body mass index (BMI) and weight. Linear regression analyses were performed to evaluate the associations between daily sedentary time and each muscular parameter, adjusting for age, sex, ethnicity, annual family income, and moderate-to-vigorous physical activity (MVPA). Results: The linear regression analyses revealed negative associations between daily sedentary time and all muscular parameters, apart from absolute ALM. These included HGS (β, -0.265; standard error [SE], 0.074; p=0.001), HGS/BMI (β, -0.021; SE, 0.004; p<0.001), HGS/weight (β, -0.008; SE, 0.002; p<0.001), ALM/BMI (β, -0.008; SE, 0.003; p=0.010), and ALM/weight (β, -0.003; SE, 0.001; p=0.005). Conclusions: After adjusting for MVPA, daily sedentary time was inversely associated with HGS, HGS/BMI, HGS/weight, ALM/BMI, and ALM/weight in United States adolescents.